Detection Of Active Female Genital Tuberculosis By Molecular Method - P. SARASWAT; M.L. SWARANKA; A. BHANDARI; R. R. SONI (International Journal of Pharma and Bio Sciences, 2010)
A molecular method for early detection of active female genital tuberculosis from clinical endometrial tissue specimens was developed by modifying single tube nested reverse transcriptase polymerase chain reaction. The reliability of this method was compared with the gold standard culture method (a combination of Mycobacterium Growth Indicator Tube system and Lowenstein Jiensen media) that is a still corner stone on which a definitive diagnosis relies. The viability of Mycobacterium tuberculosis (half-life only 2-3 min), excellent yield and purity of isolated total ribonucleic acid from clinical tissue specimens were obtained by using commercially available kits and reagents. The use of special negative control (template without reverse transcriptase enzyme) makes the modified method more reliable for diagnostic purposes, since it checks deoxyribo nucleic acid contamination. Finally, early detection of active female genital tuberculosis is possible by this modified method rather than time consuming culture methods.